Circular economy in the electrical and electronic equipment industry - Lasmane, Elizabete (Riga Graduate School of Law, 2020)
The electrical and electronic equipment waste generated in the European Union and outside of it is constantly increasing; therefore the relevance of the electronic industries shift towards a circular economy is at a peak. The main objectives of this thesis are to assess how the electrical and electronic equipment industry is moving towards circular economy and what benefits this brings to companies. In this thesis, concepts of circular economy, private sector and the electrical and electronic equipment industry are covered. Further, European Union instruments relevant are presented. An analysis of two companies, Royal Philips and Electrolux AB, is conducted to derive to good practices moving the industry towards circular economy and benefits arising from these practices. There are significant findings of a link between the good practices, such as using recycled materials, resource efficiency and others, and economic benefits favoring the company discovered.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Environmental law